2018
DOI: 10.22456/1679-9216.88860
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Findings in the Adrenal Glands of 80 Dogs

Abstract: Background: The adrenal glands development important endocrine functions and can be affected by primary or secondary diseases. These adrenal gland pathologies may induce clinical syndromes resulting from abnormalities in the production and secretion of hormones. Data about pathological changes in dogs are scarce. Therefore, the aim of the present study was to identify and evaluate the histopathological and epidemiological features of adrenal changes in dogs submitted to necropsy examination from 2005 to 2016 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…13 Consequently, distinguishing between PDH and FAT in ultrasound images is sometimes difficult due to EAA. 13 Also, dogs with HAC may present concurrent conditions including metastatic adrenal lesions, non-functional adrenal tumour, other functional tumours such as pheochromocytoma, [21][22][23] or concurrent PDH and FAT leading to EAA. 24 Furthermore, bilateral adrenal adenoma or adenocarcinoma can occur and might also result in EAA.…”
Section: Discussionmentioning
confidence: 99%
“…13 Consequently, distinguishing between PDH and FAT in ultrasound images is sometimes difficult due to EAA. 13 Also, dogs with HAC may present concurrent conditions including metastatic adrenal lesions, non-functional adrenal tumour, other functional tumours such as pheochromocytoma, [21][22][23] or concurrent PDH and FAT leading to EAA. 24 Furthermore, bilateral adrenal adenoma or adenocarcinoma can occur and might also result in EAA.…”
Section: Discussionmentioning
confidence: 99%
“…It is a common modality for diagnosing adrenal disorders, particularly in PDH, or adrenal tumors [ 2 , 6 , 7 ]. Adrenal tissue biopsy is the gold standard for classifying adrenal disorders [ 2 , 19 ]. However, both the left and right adrenal glands are located near the aorta and the caudal vena cava, which are high-risk regions for fine-needle aspiration or tissue biopsy, especially in the case of non-sedative or non-anesthetic procedures.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, PDH was also found to be more prevalent in females than in males [ 22 ]. In contrast, tumor-affected dogs were mostly male [ 1 , 19 ]. In our study, the adrenal disease was common in medium- and old-aged dogs, with slightly higher incidences among breeds and between sexes, which may be due to the small number of dogs in the study or the different geographic regions.…”
Section: Discussionmentioning
confidence: 99%
“… 6 Bilateral nodular adrenocortical hyperplasia is not common in dogs, being mainly a necropsy finding in older dogs. 21 Nonetheless, currently, there are no studies establishing the association with clinical signs, hormonal test results, and histological evaluation of the pituitary gland and CS.…”
Section: Discussionmentioning
confidence: 99%